Environmental Protection in European Law - Ivanović, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Over last decades the economic and business development as well as the accelerated industrialization and technical and technological progress coupled with the application of the new technologies and integration of all countries in European and global business, economic and traffic flows, based primarily on technological and scientific achievements gave rise to a particular level and degree of contamination of the main natural resources of the living world. Due to the great importance of regulating, improving and protecting the environment, either concerning all its aspects or just some of them (water, air, soil, flora and fauna), the international community through a number of international (Under the auspices of UN) or regional (Council of Europa and European Union) legal acts established the legal standards in the given field, that had to be implemented by certain countries, including the Republic of Serbia, into respective national legislations as an attribute of the rule of law states. It is the foundation for the determination of the Republic of Serbia as a state that strongly protects the principle of sustainable development. In this paper, the author has analysed the application of European standards in the new environmental law in the Republic of Serbia since 2005.